The Wide-Coverage Sprinkler With the Flexible Tap and Flying Machines for the Rice Sowing - R. D. Umarov; F. M. Magomedov; I. M. Melikov; D. A. Salatova; S. E. Senkevich (Сельскохозяйственные машины и технологии)
The article presents the brief analysis of existing technical determinations for spraying, the surface injection of liquid solutions, in the course of which about 75 percent of pesticides used in agricultural production are injected in order to preserve the crop from pests, diseases and weeds. (Purpose of the study) To develop the wide-coverage sprinkler with extended operational and technological capabilities for the rice sowings. (Materials and methods) It has been established that the main criterion for the up-to-date creation of the technical equipment used for spraying is the reduction of norms of the working fluid consumption and the level of environmental pollution by pesticides and also that the domesticmachines for this use coming to the market have low technical performance indicators and insufficient reliability. (Results and discussions) The design of a new wide-coverage spraying machine with a flexible tap and vehicles for the spraying of rice and with extended operational and technological capabilities, containing two propulsion units (one with a current generator, the other with a solution tank and a pressure pipeline) has been suggested. They are equipped with the frames with tensioners and are kinematically connected to each other by a flexible carcase on which the vehicles and suspended nodes of the mud channel with spraying machines are placed. The spraying of the rice fields by vehicles confirms theexpediency of their application in the rice industry for the ensuring of significant reduction in the crop losses from plant diseases. The production of new chemicals with low consumption rates and enhanced biological activity served as the basis for the development of the proposed design of wide-coverage sprinkler to meet modern requirements for sprayers of this type and intended for the use in medium and large rice farms. (Conclusions) The use of the presented wide-coverage sprinkler will allow farmers to apply intensive technology of rice cultivation on rice farms, and it will significantly increase the effectiveness of protective measures and reduce the consumption rates of chemicals, as well as reduce haul costs and spraying of working liquid solutions. The adoption of new technologies and technical means of plant protection that meetmodern requirements are worthy of continued work on their improvement and, in particular, the creation of new technicalmeans of weed control